Italian Renaissance art understanding its meaning - Joost-Gaugier, Christiane L. (Wiley-Blackwell, 2013)
"Richly illustrated, and featuring detailed descriptions of works by pivotal figures in the Italian Renaissance, this enlightening volume traces the development of art and architecture throughout the Italian peninsula in the fifteenth and sixteenth centuries. A smart, elegant, and jargon-free analysis of the Italian Renaissance - what it was, what it means, and why we should study it. Provides a sustained discussion of many great works of Renaissance art that will significantly enhance readers' understanding of the period. Focuses on Renaissance art and architecture as it developed throughout the Italian peninsula, from Venice to Sicily. Situates the Italian Renaissance in the wider context of the history of art. Includes detailed interpretation of works by a host of pivotal Renaissance artists, both well and lesser known."--Provided by publisher.